BEHAVIOURAL ACCOUNTING: AN INTRODUCTION TO UNDERSTANDING - SALLY PAULINA SANDANAFU (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2023)
This paper will briefly discuss behavioural accounting. Pragmatically, behavioural accounting is the application of social science concepts to several accounting research areas such as budgeting, decision-making, controlling, and financial reporting. This newly emerging subdiscipline tries to focus on the human element with its human nature. Although accounting is essentially a quantitative field of study. The method of this study is a literature search, with the primary data sources being related scientific journals, and also other sources compatible with the theme of this discourse. This paper provides a brief introduction to behavioural accounting.